Headache OSCE: A 22-Year-Old Woman Presents to the Emergency Department With a Severe Headache - Diana Barratt; Vivian Obeso (Association of American Medical Colleges, 2012)
Abstract This resource is a 15-minute objective structured clinical examination (OSCE) where examinee take a detailed headache history from a standardized patient, generate an initial differential diagnosis, request and interpret diagnostic tests, and defend the final diagnosis. Criteria for passing and a grading system have been established. Remediation plans are prescribed, depending on the type of error made by the examinee. The tool has content validity, as it has been developed by a neurologist and reviewed by four additional content experts. It has face validity, based on a small survey of third-year medical students. It has been administered by four different faculty members, in addition to the principal investigator. The instructions are clear and the tool is easy to use.